Download presentation

Presentation is loading. Please wait.

1
Inverse Functions

2
Objectives Students will be able to find inverse functions and verify that two functions are inverse functions of each other. Students will be able to use the graph of a functions to determine whether functions have inverse functions. Students will be able to use the horizontal line test to determine if functions are one- to-one. Find inverse functions algebraically.

3
Definition of the Inverse Function Let f and g be two functions such that f (g(x)) = x for every x in the domain of g and g(f (x)) = x for every x in the domain of f. The function g is the inverse of the function f, and denoted by f -1 (read “f-inverse”). Thus, f ( f -1 (x)) = x and f -1 ( f (x)) = x. The domain of f is equal to the range of f -1, and vice versa.

4
Example Show that each function is the inverse of the other: f (x) = 3x and g(x) = x/3. Solution To show that f and g are inverses of each other, we must show that f (g(x)) = x and g( f (x)) = x. We begin with f (g(x)). f (x) = 3x f (g(x)) = 3g(x) = 3(x/3) = x. Next, we find g(f (x)). g(x) = x/3 g(f (x)) = f (x)/3 = 3x/3 = x. Notice how f -1 undoes the change produced by f.

5
Graphing Inverses Inverses are symmetric about the line y=x To graph reverse the x and y coordinates. Use the symmetry around y = x Example; page 2117 - 118 #38, 16, 18

6
The Horizontal Line Test For Inverse Functions A function f has an inverse that is a function, f –1, if there is no horizontal line that intersects the graph of the function f at more than one point.

7
Example Does f(x) = x 2 +3x-1 have an inverse function?

8
Example Solution: This graph does not pass the horizontal line test, so f(x) = x 2 +3x-1 does not have an inverse function.

9
Finding the Inverse of a Function The equation for the inverse of a function f can be found as follows: 1.Verify the function is one-to-one (HLT). 2.Replace f (x) by y in the equation for f (x). 3.Interchange x and y. 4.Solve for y. If this equation does not define y as a function of x, the function f does not have an inverse function and this procedure ends. If this equation does define y as a function of x, the function f has an inverse function. 5.If f has an inverse function, replace y in step 3 with f - 1 (x). We can verify our result by showing that f ( f -1 (x)) = x and f -1 ( f (x)) = x.

10
Find the inverse of f (x) = 6x + 3. Solution Step 1 Replace f (x) by y. y = 6x + 3 Step 2 Interchange x and y. x = 6y + 3 This is the inverse function. Step 3 Solve for y. x - 3 = 6y Subtract 3 from both sides. x - 3 = y 6 Divide both sides by 6. Step 4 Replace y by f -1 (x). x - 3 6 f -1 (x) = Rename the function f -1 (x). Example

11
Examples Page 118 #58, 76 Page 118 #58, 76 Groups: Pg 117: # 12, 28, 30, 39, 41, 62 Groups: Pg 117: # 12, 28, 30, 39, 41, 62 Homework: Pg 117: # 1 – 41 odd, 63, 67, 75 Homework: Pg 117: # 1 – 41 odd, 63, 67, 75

Similar presentations

© 2020 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google